20 Co-production and pilot testing a web-based decision aid to support people with motor neurone disease considering a gastrostomy tube (DiAMoND Study). (14th March 2023) - Wheelwright, Sally; Maunsell, Rose; Taylor, Sophia; Drinkwater, Neil; Erridge, Clare; Foster, Claire; Hardcastle, Maggi; Hogden, Anne; Lawson, Ian; Lisiecka, Dominika; McDermott, Christopher; Morrison, Karen; et al.
Abstract : Introduction: A gastrostomy tube (GT) may be offered to people living with motor neurone disease (plwMND) to administer food, fluids and medication when eating and drinking become difficult. However, the evidence base for GT benefit is lacking. Patient decision aids (DA) support shared decision making by providing evidence-based information, elucidating personal preferences and checking understanding. 1 Methods: The three-phased DiAMoND study aimed to co-produce and pilot test a web-based DA to support people with MND deciding whether to have a GT. Participants included plwMND, carers and healthcare professionals (HCPs). In Phase 1, the content and design of the DA was informed by semi-structured interviews, literature reviews and prioritisation survey. In Phase 2, the prototype DA was tested with users and developed iteratively with feedback from surveys and 'think-aloud' interviews. In Phase 3 the DA was evaluated using validated questionnaires. 2–5 Results: In total, 16 plwMND, 16 carers and 25 HCPs took part in Phases 1 and 2. Interviews and the literature review generated a prioritisation survey with 82 content items. Seventy-seven percent (63/82) of the content of the DA was retained. A prototype DA, which conforms to international DA standards1, was produced and improved during Phase 2. In Phase 3, 17 plwMND completed questionnaires after using the DA. Most plwMND (94%) found the DA completely acceptable and would recommend it to others in their position, had no decisional conflict (88%), and were well prepared (82%) and satisfied with their decision making (100%). Conclusion: Gastrostomy Tube: Is it for me? was co-produced with stakeholders and found to be acceptable, practical and useful to plwMND. It is freely available from the MND Association website. The DA is a valuable tool to support plwMND and HCPs through the GT shared decision making process. References: International Patient Decision Aid Standards (IPDAS) (Accessed June 23, 2022, at www.ipdas.ohri.ca.) O'Connor A. User Manual – Stage of Decision Making 2000 [updated 2003] [Available from: https://decisionaid.ohri.ca/docs/develop/user_manuals/um_stage_decision_making.pdf]. Ferron Parayre A, Labrecque M, Rousseau M, Turcotte S, Légaré F. Validation of SURE, a four-item clinical checklist for detecting decisional conflict in patients. Medical Decision Making : An International Journal Of The Society For Medical Decision Making . 2014;34 (1):54–62. C Bennett, ID Graham, E Kristjansson, SA Kearing, KF Clay, O'Connor A. Validation of a preparation for decision making scale. Patient Educ Couns . 2010;78 (1):130–3. Holmes-Rovner M, Kroll J, Schmitt N, Rovner DR, Breer ML, Rothert ML, et al . patient satisfaction with health care decisions:the satisfaction with decision scale. Medical Decision Making . 1996;16 (1):58–64.